Recent insights in the correlation between social media use, personality traits and exercise addiction: a literature review - Minutillo, Adele; Di Trana, Annagiulia; Aquilina, Valeria; Ciancio, Gerolama Maria; Berretta, Paolo; La Maida, Nunzia (Frontiers in Psychiatry, 2024)
Introduction and aim: The excessive involvement in physical activity without stopping in between sessions despite injuries, the continuous thinking to exercise feeling insane thoughts and experiencing withdrawal symptoms are all characteristics of the Exercise Addiction (EA), an addictive behavior. While the primary exercise addiction is directly caused by compulsive exercise, many studies highlighted the relationship between Eating Disorders (ED) and EA, defining the secondary EA. The correlation between EA, social media use (SMU) and other individual traits remains a relatively underexplored domain. Therefore, this review aimed to examine the latest evidence on the relationship between EA, SMU, and some personality traits such as perfectionism and body image. Methods: Electronic databases including PubMed, Medline, PsycARTICLES, Embase, Web of Science were searched from January 2019 to October 2023, following the PRISMA guidelines. Results: A total of 15 articles were examined and consolidated in this review. EA was found to be related to different individual traits such perfectionism, body dissatisfaction, depression, obsessivecompulsive personality disorders. While controversial results were found regarding the relationship between EA and SMU. Conclusion: The interaction between mental health, exercise addiction and social media use is complex. Excessive engagement in these latter may result in negative mental health consequences despite their potential benefits. Understanding individual differences and developing effective interventions is crucial to promoting healthy habits and mitigating the EA risks, ultimately enhancing mental well-being. Further research should focus on the identification of risks and protective factors with the eventual aim of developing and implementing effective prevention strategies.